Dança e espetacularidade: processo artístico-religioso do grupo botões da rosa na festividade de Santa Rosa de Lima, Abaetetuba - PA - SERRÃO, Letícia Maria Pinheiro (2023)
This course completion work emerged from my involvement as a teacher- catechist in the Botões da Rosa dance group, from the parish of Santa Rosa de Lima, in Abaetetuba/PA. The research aimed to understand the spectacularity and choreographic process of the Botões da Rosa group at the Festivity of Santa Rosa de Lima, from July to August 2022. I emphasize that the group performs at religious festivals such as feasts of saints and, mainly , I emphasize that it is a Catholic group. As a theoretical- methodological reference I used the studies of Ethnoscenology that studies spectacular practices and behaviors, according to Pradier (1999), through the studies of Bião (2009) and Santa Brígida (2014). To deal with dance, I used the author Kassing (2016), mainly because she uses classical ballet movements as a choreographic inspiration and on the creation process, I focused on the authors Lobo and Navas (2003) and (2008). The approach was qualitative, focusing on ethnocenology, in order to discuss the choreographic process. As a methodological strategy, 03 people from the parish of the community were interviewed, and the children and adolescents who are part of this group were not interviewed directly, but their bodies served as support for this research. As a result, I present the processes that involve a choreographic composition in religious dance, ways and methods to arrive at the composition of the show Flores de Santa Rosa, performed at Auto da Rosa on August 23, the date that celebrates the day of this saint, considered the first saint of Latin America.